2014 Consensus Statement from the first Economics of Physical Inactivity Consensus (EPIC) Conference (Vancouver). Issue 12 (23rd May 2014) - Davis, Jennifer C; Verhagen, Evert; Bryan, Stirling; Liu-Ambrose, Teresa; Borland, Jeff; Buchner, David; Hendriks, Marike RC; Weiler, Richard; Morrow, James R; van Mechelen, Willem; Blair, Steven N; Pratt, Mike; et al.
Abstract : This article describes major topics discussed from the 'Economics of Physical Inactivity Consensus Workshop' (EPIC), held in Vancouver, Canada, in April 2011. Specifically, we (1) detail existing evidence on effective physical inactivity prevention strategies; (2) introduce economic evaluation and its role in health policy decisions; (3) discuss key challenges in establishing and building health economic evaluation evidence (including accurate and reliable costs and clinical outcome measurement) and (4) provide insight into interpretation of economic evaluations in this critically important field. We found that most methodological challenges are related to (1) accurately and objectively valuing outcomes; (2) determining meaningful clinically important differences in objective measures of physical inactivity; (3) estimating investment and disinvestment costs and (4) addressing barriers to implementation. We propose that guidelines specific for economic evaluations of physical inactivity intervention studies are developed to ensure that related costs and effects are robustly, consistently and accurately measured. This will also facilitate comparisons among future economic evidence.